EPEN-29. INDIVIDUALIZED THERAPY OF AN ANAPLASTIC EPENDYMOMA PEDIATRIC PATIENT WITH A NOTCH1 GERMLINE MUTATION. Issue 2 (22nd June 2018) - Russo, Alexandra; Paret, Claudia; Lehmann, Nadine; Bender, Hannah; Wingerter, Arthur; Neu, Marie Astrid; Alt, Francesca; Backes, Nora; Roth, Lea; Seidmann, Larissa; Faber, Jörg
Abstract: The treatment of relapsed pediatric cancers represents a challenge, also due to possible underlying rare germline mutations. The introduction of next sequencing technologies allows a deeper understanding of molecular mechanisms involved in cancer progression helping in the identification of personalized therapies for these patients. However, most tumors harbor several pathway alterations and it is necessary to prioritize the treatment options. Here we applied the concept of personalized therapy to a pediatric patient with an anaplastic ependymoma and who relapsed three times under standard chemio and radiotherapy. By RNA sequencing we identified in the tumor a Notch1 mutation which was confirmed by Sanger Sequencing and which was also present in the blood DNA. Pathway analysis revealed an activation of the sonic hedgehog (SHH), the WNT, the IGF and the Notch pathway. In an attempt to prioritize possible targeted therapies, we treated the patient-specific tumor cells with relevant inhibitors in vitro. The cells were particularly sensitive to Arsenic Trioxide, an inhibitor of the SHH pathway, and to ceritinib, an off-target inhibitor of IGF-1R. Combination of Arsenic Trioxide with chemotherapy reduced the growth rate of the tumor. However, because we were not able to reach the needed Arsenic concentration in CSF, we switched to ceritinib. The patient is currently receiving the first cycle of ceritinib and chemotherapy. In the era of personalized medicine, the molecular analysis of the tumor and the use of patient-specific tumor cells may represent a powerful tool to identify new therapeutic treatments for patients with underlying rare mutations.